Potent inhibition of miR-27a by neomycin-bisbenzimidazole conjugates - Nahar, Smita; Ranjan, Nihar; Ray, Arjun; Arya, Dev P.; Maiti, Souvik (Chemical Science, 2015)
miRNAs are important components of regulatory networks that control gene expression and have implications in various diseases including cancer. Targeting oncogenic miRNAs with small molecules is currently being explored to develop cancer therapeutics. Here, we report the development of dual binding neomycin-bisbenzimidazole conjugates that target oncogenic miR-27a with high affinity (K-a = 1.2 to 7.4 x 10(8) M-1). These conjugates bring significant reduction (similar to 65% at 5 mu M) in mature miRNA levels and penetrate easily in the cells where they localise both in the cytoplasm and the nucleus. Cell cycle analysis showed significant increase in the G0/G1 phase (similar to 15%) and decrease in the S phase (similar to 7%) upon treatment with neomycin-bisbenzimidazole conjugates, suggesting inhibition of cell proliferation. Using the conjugation approach, we show that moderately binding ligands can be covalently combined into high affinity binders. This study also highlights the role of linker optimization in designing high affinity ligands for miR-27a targeting.